Down Syndrome and Other Chromosome Abnormalities - Kumar Dey, Subrata (IntechOpen, 2022)
This book provides a concise yet comprehensive source of current information on Down syndrome and other chromosomal abnormalities. Research workers, scientists, medical graduates and paediatricians will find it an excellent source for reference and review. Key features of this book are as follows: • Mechanisms of aneuploidy. • Effect of sociodemographic factors on different congenital disorders. • Haematological malignancies and congenital heart disease in Down syndrome. • Prenatal screening, management and counselling to detect Down syndrome and other chromosomal abnormalities. While aimed primarily at research workers on Down syndrome and different types of chromosomal disorders, we hope that the appeal of this book will extend beyond the narrow confines of academic interest and be of interest to a wider audience, especially the parents and relatives of children suffering from Down syndrome and other chromosomal abnormality syndromes.